2022
DOI: 10.1021/acsestwater.2c00041
|View full text |Cite
|
Sign up to set email alerts
|

Self-Accelerated Photodegradation of 2,4-Dihydroxybenzophenone in Water: Formation of Photoactive Products and Implications for the Transformation of Coexisting Organic Contaminants

Abstract: Benzophenone (BP) UV filters are a group of contaminants of emerging concern. In this study, we found that 2,4-dihydroxybenzophenone (BP1) was more liable to photodegradation than the other BPs. Particularly, an accelerated degradation of BP1 was observed under UV365nm irradiation. Singlet oxygen (1O2) was identified as the key reactive species leading to its degradation. Generation of 1O2 was mostly ascribed to certain photodegradation products of BP1. These products have an aromatic ketone structure and can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similar to DOM, the chromophores in the root exudates could absorb light and generate reactive species (RS), typically including the triplet excited state of DOM ( 3 DOM*) and reactive oxygen species (ROS, e.g., 1 O 2 and · OH). 3 DOM* can react directly with organic contaminants via energy, electron, or hydrogen atom transfer reactions Thus, the RS play important roles in the photosensitized degradation of organic contaminants in waters. There are studies that reported that wetland-derived organic matter was conducive to enhancing the production of RS compared to that of some standard DOMs (e.g., Suwannee River fulvic acid). , It is known that these photoinduced RS are mainly derived from the oxygen-containing groups of DOM (e.g., ketones, quinones, and carboxylate-substituted phenols), , which varied from the root exudates of aquatic plants .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to DOM, the chromophores in the root exudates could absorb light and generate reactive species (RS), typically including the triplet excited state of DOM ( 3 DOM*) and reactive oxygen species (ROS, e.g., 1 O 2 and · OH). 3 DOM* can react directly with organic contaminants via energy, electron, or hydrogen atom transfer reactions Thus, the RS play important roles in the photosensitized degradation of organic contaminants in waters. There are studies that reported that wetland-derived organic matter was conducive to enhancing the production of RS compared to that of some standard DOMs (e.g., Suwannee River fulvic acid). , It is known that these photoinduced RS are mainly derived from the oxygen-containing groups of DOM (e.g., ketones, quinones, and carboxylate-substituted phenols), , which varied from the root exudates of aquatic plants .…”
Section: Introductionmentioning
confidence: 99%
“…Solutions of each pollutant (10.0 μM) were prepared in each plant's root exudate from 5.0 mM stock aqueous solutions. Quenching experiments were performed with the addition of sorbate (2.5 mM), FFA (10.0 mM), and isopropanol(10…”
mentioning
confidence: 99%